THERMAL TEST OF 3D PRINTING FILAMENTS FROM PLASTIC WASTE AS AN ENVIRONMENTALLY FRIENDLY PRINTING MEDIA ALTERNATIVE - Apriliani, Melinda (Kreator, 2023)
Plastic is an alkene polymer compound with very large molecules. The more people use it, the more waste is released. One way to reduce plastic waste in Indonesia can be done by recycling. In this way, you can minimize HDPE waste that is no longer used.Processing plastic waste in industry can be done by making 3D printing filaments. With 3D printing technology, companies can make a prototype without having to spend raw materials or materials. This research aims to analyze the thermal test results of waste HDPE bottle caps and thermoplastics which are used by utilizing recycled bottle caps as a thermoplastic mixture with different formulation variations. The research method that will be used consists of several stages, namely: 1). Sorting of HDPE plastic bottle caps; 2) Grinding; 3) Extrusion process 4) 3D Printing filament diameter measurement test 5) Test run..